2012
DOI: 10.1088/0953-2048/26/2/025004
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric superconducting spin valves based on the Fe/V layer system grown on MgO(100)

Abstract: We studied asymmetric superconducting spin valves with the layer sequence V/Fe/V/Fe/CoO, grown on MgO(100). These thin film heterostructures exhibit a superconducting spin valve (SSV) effect, that is, a difference, T s , between the superconducting transition temperatures T s with the magnetization directions of the two Fe layers oriented antiparallel and parallel. For pure Fe layers in the SSV we observe a maximum shift T s = 24 mK. On replacing the Fe layers with FeV alloy layers, the SSV effect was increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 40 publications
2
10
0
Order By: Relevance
“…Structures similar to suggested by Oh et al [1] were investigated to a less extent. A studied [Fe/V] n antiferromagnetically coupled superlattice with thick superconducting vanadium layer on the top instead of a single F1/N/F2 trilayer [22][23][24] was not actually the spin valve device because the system could not be switched from the AP to P orientation of the magnetizations instantaneously. At the same time the analysis of the temperature dependence of the critical field has shown that implicitly ∆T c of this structure can reach up to 200 mK at δT c ∼100 mK.…”
Section: B Superconducting Spin Valvementioning
confidence: 99%
“…Structures similar to suggested by Oh et al [1] were investigated to a less extent. A studied [Fe/V] n antiferromagnetically coupled superlattice with thick superconducting vanadium layer on the top instead of a single F1/N/F2 trilayer [22][23][24] was not actually the spin valve device because the system could not be switched from the AP to P orientation of the magnetizations instantaneously. At the same time the analysis of the temperature dependence of the critical field has shown that implicitly ∆T c of this structure can reach up to 200 mK at δT c ∼100 mK.…”
Section: B Superconducting Spin Valvementioning
confidence: 99%
“…Despite the ultra-small E ex in comparison even with weak TM ferromagnets, we see a very large reversible ∆T c0 ≈ 400 mK which is in quantitative agreement with the theoretical model. Previous theories suggested that to get a sizable ∆T c0 it is crucial to have a high interface transparency, a small pair-breaking scattering, and a large superconducting coherence length because Cooper pairs have to sense the exchange field from both F layers [8,10,19]. The fully epitaxial nature of our SSVs should improve interface quality and hence provide a reasonably high interface transparency and a small interface scattering as evidenced by the small dimensionless interfacial resistance γ b ~ 0.3.…”
mentioning
confidence: 91%
“…The superconducting spin valve (SSV) exploits proximity-coupling between a superconductor and two ferromagnet (F) layers such that the exchange-induced suppression of the critical temperature (T c ) is controlled by the relative magnetization orientation of the F layers [2-5]. To date, experimental realization of this effect [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] has been limited to transition metal (TM) F layers and the maximum ∆T c between parallel (P) and antiparallel (AP) orientation is about 40 mK, with a T c below 0.4 K [9]. Although ∆T c was improved to 200 mK with a T c around 2.8 K, this was obtained in a large (kOe) field [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…for F/S/F and S/F/F structures), the superconducting transition temperature depends on the relative orientation of their magnetizations 26,27 . Such systems represent superconducting spin valves, which can be switched between two states with different transition temperatures by magnetic fields, as demonstrated experimentally for the F/S/F [28][29][30] and S/F/F [31][32][33] case. For non-collinear orientations of the magnetizations, an unconventional odd-in-frequency triplet s-wave pairing 23 is predicted, reducing the superconducting transition temperature 34 .…”
Section: Introductionmentioning
confidence: 99%